2022
DOI: 10.1590/fst.64722
|View full text |Cite
|
Sign up to set email alerts
|

Research on identification method of tangerine peel year based on deep learning

Abstract: Tangerine Peel has rich medicinal value, known as ' one kilogram of tangerine peel, one kilogram of gold '. However, the value of tangerine peels in different years is different, and there is no significant difference in the appearance of tangerine peels in different years. Identifying their authenticity has brought trouble to the industry. Generally speaking, the characteristics of tangerine peel can be identified through the texture, color and oil parcel points on the surface of tangerine peel. However, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In the past few years, the image classifcation of agricultural products represented by tangerine peel is emerging. Chu et al introduced a method to increase the data volume of tangerine peel by utilizing traditional data augmentation, deep convolution generative adversarial networks (DCGAN), and Mosaic [17]. Te data volume of the original sample was increased by 23 times.…”
Section: Related Workmentioning
confidence: 99%
“…In the past few years, the image classifcation of agricultural products represented by tangerine peel is emerging. Chu et al introduced a method to increase the data volume of tangerine peel by utilizing traditional data augmentation, deep convolution generative adversarial networks (DCGAN), and Mosaic [17]. Te data volume of the original sample was increased by 23 times.…”
Section: Related Workmentioning
confidence: 99%
“…, Mahamudul Hashan et al (2022 proposed a multilayer convolutional neural network MCNN to classify three apple leaf diseases, and the experimental results showed that the model achieved an accuracy of 98.4%. In 2022, Chu et al (2022) proposed a Chenpi-year recognition method based on deep learning. They used data-enhanced dataset and an improved ResNet50 model to accurately identify the year of tangerine peels.…”
Section: An Apple Leaf Disease Identification Model For Safeguarding ...mentioning
confidence: 99%
“…With the continuous development of technology, the ability and intelligence of computers to process information are also improving, and neural network technology has also been greatly developed. Neural network technology has been used in different fields, such as food technology (Xu et al, 2022) and automatic control (Bai et al, 2022). Krizhevsky et al (2017) proposed AlexNet in 2012 and won the ImageNet classification competition.…”
Section: Introductionmentioning
confidence: 99%
“…By designing different weight layers, neural network models with different depths can be established, such as VGG (Simonyan & Zisserman, 2014), GoogleNet (Szegedy et al, 2015) and ResNet (Chu et al, 2022;He et al, 2016). Although deeper networks may achieve higher accuracy, the training and inference speed of the model will decrease.…”
Section: R-cnn Backbonementioning
confidence: 99%